The Main Plaza Design For Al-Amin Living Lab And Industrial Park In Sampe Cita Village - Fariz Harindra Syam; Dara Wisdianti; Melly Andriana; Syahna Dwi Ardianti (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This research was conducted to design Plaza Utama Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District to fulfill the space needs and requirements. The design of Al-Amin Main Plaza Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District can create the flexibility of the desired space and shape. Plaza is a word derived from Spanish which has a meaning related to “field”. Plaza can be described as an open space for the public (public space) that can be found in urban areas or a region. Sustainable architecture, also known as green architecture, is an architectural concept that seeks to minimize the negative impact of the building environment with efficiency and moderation in the use of materials, energy, and development space and ecosystem at large. The development of Al-Amin Living Lab and Industrial Park is adjusted to the plans and concepts that have been made. The detailed design of the area to be created must follow the rules of the concept of sustainability and local wisdom. Every building that will be built in this area must have an environmentally friendly and energy-efficient concept. The design of the Main Plaza of Al-Amin Living Lab and Industrial Park follows the rules of sustainable architectural design. This is shown by the use of environmentally friendly materials and designs that are in harmony with the environment. The design concept of the Main Plaza of Al-Amin Living Lab and Industrial Park also refers to the masterplan of the area that has been made before.